2019
DOI: 10.1021/acs.jced.9b00177
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria and Phase Diagrams for the Aqueous Ternary System Containing Sodium, Sulfate, and Metaborate Ions at 288.15 and 308.15 K and 101.325 kPa

Abstract: Solubilities and physicochemical properties (density and refractive index) for the ternary system (Na+//SO4 2–, BO2 –-H2O) at (288.15 and 308.15) K and 101.325 kPa were studied by the isothermal dissolution equilibrium method. Phase diagrams and diagrams of the physicochemical properties (density and refractive index) were plotted against the concentration of sodium sulfate. For both temperatures, the phase diagrams contained one invariant point, two univariant curves, and two crystallization regions correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…The form of boron species is affected by the pH, temperature, solution concentration, and so forth. The phase equilibrium of systems containing metaborate at multitemperatures has been reported, such as (NaCl + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, , (Na 2 SO 4 + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, , (NaOH + NaBO 2 + H 2 O) and (KOH + KBO 2 + H 2 O) at (283.15, 298.15, and 323.15) K, and (KBO 2 + LiBO 2 + H 2 O) and (NaBO 2 + LiBO 2 + H 2 O) at 298.15 K . The system (NaBO 2 + KBO 2 + H 2 O) is not only one of the most indispensable subsystems of the complex composition in Chaerhan Salt Lake brines, which should be studied primarily, but also is the theoretical guidance for separating boron salts from the brines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form of boron species is affected by the pH, temperature, solution concentration, and so forth. The phase equilibrium of systems containing metaborate at multitemperatures has been reported, such as (NaCl + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, , (Na 2 SO 4 + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, , (NaOH + NaBO 2 + H 2 O) and (KOH + KBO 2 + H 2 O) at (283.15, 298.15, and 323.15) K, and (KBO 2 + LiBO 2 + H 2 O) and (NaBO 2 + LiBO 2 + H 2 O) at 298.15 K . The system (NaBO 2 + KBO 2 + H 2 O) is not only one of the most indispensable subsystems of the complex composition in Chaerhan Salt Lake brines, which should be studied primarily, but also is the theoretical guidance for separating boron salts from the brines.…”
Section: Introductionmentioning
confidence: 99%
“…Because the behavior of boron dissolution is very complex, borate exists in aqueous solution in the form of different species, such as 5 The form of boron species is affected by the pH, temperature, solution concentration, and so forth. The phase equilibrium of systems containing metaborate at multitemperatures has been reported, such as (NaCl + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, 6,7 (Na 2 SO 4 + NaBO 2 + H 2 O) at (288.15, 298.15, and 308.15) K, 7,8 (NaOH + NaBO 2 + H 2 O) and (KOH + KBO 2 + H 2 O) at (283.15, 298.15, and 323.15) K, 9 and (KBO 2 + LiBO 2 + H 2 O) and (NaBO 2 + LiBO 2 + H 2 O) at 298.15 K. 5 The system (NaBO 2 + KBO 2 + H 2 O) is not only one of the most indispensable subsystems of the complex composition in Chaerhan Salt Lake brines, which should be studied primarily, but also is the theoretical guidance for separating boron salts from the brines. Aiming to utilize effectively the valuable potassium and boron brine resources, the phase equilibria of the ternary system (NaBO 2 + KBO 2 + H 2 O) at (298.15 and 323.15) K were determined, which can offer essential data for clarifying the formation and evolution law and formulating the process of extracting potassium and boron.…”
Section: Introductionmentioning
confidence: 99%
“…There are four boundary ternary subsystems in this quaternary system (Li + Na + Cl + BO 2 + H 2 O), which are (LiCl + LiBO 2 + H 2 O), (NaBO 2 + LiBO 2 + H 2 O), (NaCl + NaBO 2 + H 2 O), and (NaCl + LiCl + H 2 O). , The measured solubility data of three ternary systems are shown in Table , and the ternary system (NaBO 2 + LiBO 2 + H 2 O) was determined in this work. The deviation of measured solubility data obtained with previous reports is less than 0.05%, suggesting that our experimental procedure and results are rational and reliable.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the NaBO 2 + Na 2 SO 4 + H 2 O system, only Skvortsov et al and Chen et al , reported the experimental solubility data. At 298.15 K, the solubility isotherm reported by Skvortsov et al is significantly different from the recent data of Chen et al and indicates the formation of a double salt NaBO 2 ·Na 2 SO 4 ·14H 2 O and a solid solution m NaBO 2 · n Na 2 SO 4 · x H 2 O.…”
Section: Thermodynamic Modelingmentioning
confidence: 99%